Rynek pracy sektora rolniczego województwa warmińsko-mazurskiego - Grzywińska-Rąpca, Małgorzata (Agricultural Sector Labour Market in Warmia and Mazury Province, 2006)
The situation on the labour market is the result of influence of many complex economic processes. At the top of their list economic growth rate and linked to it, currently small, increase in the number of available jobs should be mentioned. Changes in the structure of demand for labour is basically assessed according to economic sectors, ownership sectors and individual types of economic activity. The need to decrease employment in agriculture and to increase it in non-agricultural sectors is the key problem for Polish economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 295-298